Complete genome sequence of Pseudomonas sp. strain SGAir0191, isolated from tropical air collected in Singapore - Wong, Anthony (2020)
Pseudomonas sp. strain SGAir0191 was isolated from an air sample collected in Singapore, and its genome was sequenced using a combination of long and short reads to generate a high-quality genome assembly. The complete genome is approximately 5.07 Mb with 4,370 protein-coding genes, 19 rRNAs, and 73 tRNAs.